Can spray freeze-drying improve the re-dispersion of crystalline nanoparticles of pure naproxen? - Braig, Veronika; Konnerth, Christoph-Günther; Peukert, Wolfgang; Lee, Geoffrey (International Journal of Pharmaceutics, 2019)
Spray freeze drying (SFD) was used to prepare re-dispersible powders of crystalline, pure-drug nanodispersions of naproxen in lactose and stabilized with hydroxypropyl cellulose. The particle size of the rehydrated powders was determined using static light scattering/Mie analysis. The nanoparticles present in the SFD powders were aggregated but could be dispersed on re-dispersion with water and stirring either with or without additional ultrasonic treatment. The disaggregation of the SFD nanoparticles was superior to that reported in the literature for spray dried nanoparticles of the same composition. It appears that the moderately-rapid freezing of the large spray droplets in LN2 during SFD produces less aggregation than does evaporative drying of the much smaller droplets during spray drying. Re-dispersion was also found to depend strongly on the pH of the original nanodispersion. The solubility of this weak acid is greater at higher pH which resulted in formation of a dissolved fraction of drug in the nanodispersions during media milling. After SFD, the dissolved naproxen fraction formed an amorphous solid which re-dissolves on re-hydration whereas the crystalline nanoparticles disaggregate.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Nanoparticles; Particle size; Poorly soluble drug; Re-dispersion; Spray freeze drying